Studi Eksperimental Laju Pertumbuhan Fouling Pada Pelat Besi Dan Alumunium Dengan Metode Pelapisan Cat Dan Lilin - Mohammad Wahyu Dwi Setiawan; Amjad Mulkus Fadlurrohman; Grandys Prameswari; Wazirotus Sakinah (Program Studi Teknik Kelautan Universitas Abdurachman Saleh Situbondo, 2023)
The majority of offshore buildings are made of metal materials such as steel, aluminum, and so on. Metallic materials have the potential for damage due to corrosion and fouling growth. This requires regular maintenance and repair to prevent damage to an offshore building structure. Therefore, research was conducted on the rate of fouling growth through the mechanism of testing steel and aluminum materials using the iron paint coating method and wax as an inhibitor with the immersion method in marine waters in the Marina Boom beach area of Banyuwangi Regency. The results obtained in this study are the Daily Growth Rate (DGR) value. The highest DGR value is on steel material using iron paint coating with a value of 0.1828 grams. The lowest DGR value is in aluminum material using wax coating with a value of 0.0744 grams. So it can be concluded that aluminum material has better resistance to fouling growth compared to steel material and the coating method using wax is more effective for inhibiting or as an inhibitor of fouling growth compared to iron paint.